ANALYSIS ON RUNS OF DAILY RETURNS IN ISTANBUL STOCK EXCHANGE - ŞENSOY, Ahmet (Journal of Advanced Studies in Finance, 2012)
The aim of this paper is to obtain some statistical properties about runs of daily returns of ISE30, ISE50 and ISE100 indices and compare these results with the empirical stylized facts of developed stock markets. In this manner, all time historical daily closing values of these indices are studied and the following observations are obtained: Exponential law fits pretty well for the distribution of both run length and magnitude of run returns. Market is equally likely to go up or go down every day. Market depth has improved over recent years. Large magnitudes of run returns are more likely to be seen in positive runs. As in the developed stock markets, daily returns in Istanbul Stock Exchange don’t have significant autocorrelations but absolute values (i.e. magnitudes) of daily returns exhibit strong and slowly decaying autocorrelations up to several weeks suggesting volatility clustering. Similar to the absolute daily returns, absolute value of run returns display strong and slowly decaying autocorrelations which again supporting the existence of volatility clustering. Unlike magnitudes of run returns, lengths of runs don’t have significant autocorrelations.